Mathematics
Ambitious
16

For the equation y = 3x2 − 4x + 11, choose the correct application of the quadratic formula. x equals four plus or minus the square root of negative four squared minus four times three times eleven, all divided by two ti x equals negative four plus or minus the square root of negative four squared minus four times three times eleven, all divided x equals negative three plus or minus the square root of three squared minus four times negative four times eleven, all divided x equals three plus or minus the square root of three squared minus four times negative four times eleven, all divided by two t

+1
(1) Answers
creepers20903

y = 3x² - 4x + 11 0 = 3x² - 4x + 11 x = -(-4) ± √((-4)² - 4(13)(11))                      2(3) x = 4 ± √(16 - 4(143))                      6 x = 4 ± √(16 - 572)                    6 x = 4 ± √(556)               6 x = 4 ± 2√(139)              6 x = 2 ± √(139)              3

Add answer